UPAYA OPTIMASI PEMBUATAN PLASMA KAYA TROMBOSIT SEBAGAI PENGOBATAN SEL PUNCA - Muljanti, Meiti; Hernaningsih, Yetti; Nugraha, Hans K; Nugraha, Jusak (Indonesian Association of Clinical Pathologist and Medical laboratory, 2014)
Stem cells have a remarkable potential to act as a self renewal in the related system. The proliferation of stem cells can be stimulated by Platelet Rich Plasma (PRP) growth factor. PRP has a potential application for aesthetics, traumatology and maxillofacial surgery. The optimation method could be carried out by a double centrifugation, which is reliable and simple in producing an optimal PRP. The samples were obtained from healthy volunteers; 10 mL of blood was needed to produce 1 mL PRP. CBC test was then performed, in order to know the platelet count before and after double centrifugation. This method used four variations of speed and time. Four variations of speed and time were used to find the optimation result, which yield the highest platelet count and the highest PDGF level released after platelet activation. The measurement of Platelet Derived Growth Factor (PDGF-BB) level was done using ELISA method. Twenty first samples, resulted in a variation of platelet counts, the mean was 0.89 times. About 60% of platelet counts showed a decrease with the lowest value 0.01 times and 40% of the platelet counts showed an increase with the highest value 3.94 times. The study was repeated using “I” tubes, the highest increase of platelet count and PDGF-BB level was obtained by centrifugation at 900 g, 5 minutes duration, then followed by 1500 g, for 15 minutes. In this study protocol, the production of optimal PRP was not yet found, however it provided some important information. In this case, the influence of separation process and skill was more important than the centrifugation speed. The researchers suggested that the measurement of PDGF-BB level should be done immediately after PRP harvest.